WORK STRESS MEDIATES THE EFFECT OF ROLE CONFLICT ON CYBERLOAFING BEHAVIOUR - Rizqi, Muhammad Wahyu; Swasti, Ika Korika (PT Larva Wijaya Penerbit, 2025)
Cyberloafing is a form deviant workplace behaviour that has become increasingly prevalent, particularly among Generation Z employees. This study aims to examine the effect of role conflict on cyberloafing behaviour, as well as the role of work stress as a mediating variable in this relationship. The research employed a quantitative approach involving 90 respondents who are Generation Z employees in Sidoarjo. Data were collected through questionnaires and analysed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method with the assistance of SmartPLS software. The result indicate that role conflict has a positive and significant effect on cyberloafing behaviour. Furthermore, work stress was found to have a significant mediating role in bridging the relationship between role conflict and cyberloafing behaviour.